Komunikasi Interpersonal Pendamping di Nurani Perempuan Women's Crisis Center dengan Korban Kekerasan Seksual di Sumatera Barat - Winda Vanisya; Elva Ronaning Roem; Sarmiati Sarmiati (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
The number of reported cases of sexual violence is still not directly proportional to the existing reality. Many of the victims deliberately chose to remain silent about the events they experienced. This is based on the condition of the victim who has no friends to tell her about her feelings of confusion, fear, and lack of knowledge about what to do after the sexual violence that happened to her. This article discusses the interpersonal communication of companions in Nurani Perempuan with victims of sexual violence in West Sumatra. This study aims to analyze interpersonal communication activities by Nurani Perempuan Women's Crisis Center as a companion with victims of sexual violence in West Sumatra. This study uses a constructivist paradigm with a case study research approach. Methods of collecting research data by conducting observations, in-depth interviews with assistants to victims of sexual violence at Nurani Perempuan, and documentation. The results of the study show that the interpersonal communication from the companion to the victims is not completely the same. In order for the victim to want to talk in depth about what happened to them, the companion must gain the trust of the victim. The communication process is also influenced by gender, character, and also the type of case experienced by each victim. Nurani Perempuan companion in the recovery of victims also always listens to victims' stories and shows a willingness to help victims so they can get up and move on with their lives.